English Proficiency Test and Academic Performance in Purposive Communication: A Correlation Study - Galang, Ruby T.; Arrozal, Jocelyn Y.; Lumanlan, Arnold D.; Cortez, Leila (Future Science / FSH-PH Publications, 2024)
English is a critical subject in the Philippines; teachers themselves are also required to pass the English Proficiency Test before practic-ing in public schools. However, there has been a gradual decline in English language proficiency among Filipinos, as evidenced by vari-ous assessments. The study aims to explore the English proficiency of college students at the university in relation to the course Purpos-ive Communication which sought to answer the following ques-tions:1) What is the academic performance in Purposive Communi-cation course of the respondents?; 2) What are the English profi-ciency level test results of the respondents? 3) Is there a significant relationship between the general weighted average in the Purposive Communication course of the respondents and the English profi-ciency level test results of the respondents? The researchers utilized a correlational research design for the study to measure the rela-tionship between independent and dependent variables; it deter-mined that a correlational design was appropriate and beneficial. This phase statistical insights into the relationship between aca-demic performance and English proficiency. The findings contribut-ed to theory generation by shedding light on the role of specific col-lege courses in shaping English proficiency and informing educa-tional policies aimed at enhancing language proficiency among fu-ture teachers.